The Personal Touch: Mackenzie King, Harriett Reid, and the Springhill Strike, 1909-1911 - Baker, William M. (Labour / Le Travail, 1984)
Introduces correspondence between Mackenzie King, who was then Minister of Labour, and Harriett Reid, who formerly worked for the United Mine Workers of America but was at the Mining Investigation Commission of Illinois, on the UMWA strike at Springhill, Nova Scotia, that ended in the workers' defeat in 1911. Argues that their comments on individuals in management and union leadership positions during the conflict illustrate the importance of personality and character when caught up in such historic events.